Hubungan Implementasi Kebijakan Transaksi Non Tunai dengan Fraud dan Kinerja Bendahara (Persepsi - Orbita Sandyasmoro, Tuah (Jurnal Ilmiah Administrasi Publik, 2021)
This study analyzes perceptions of the implementation of the non-cash transaction policy in the Magetan Regency Government, which is focused on expenditure transactions, by examining its relationship with fraud and treasury performance. The research was conducted with quantitative approach with a survey methods (census techniques) to obtain perceptions from treasurers of expenditure. Data were analyzed with SEM-PLS using the software SmartPLS. The results of the study revealed that the implementation of the non-cash transaction policy was perceived to have been implemented well in terms of the dimensions of communication, resources, disposition and bureaucratic structure. Several factors need to be improved related to regulations, implementation standards, human resources, and infrastructure. Hypothesis test results show that the implementation of this policy has no significant effect on fraud even though the direction of the relationship is theopposite, but it has a significant positive effect on the performance of treasurer ofexpenditure.